Modern Web Semantic Application For Selling Fish - Marselina Endah (International Journal of Informatics and Computation, 2020)
Betta fish is famous as a fighter fish with a difference between betta fish with other types of fishes. Many people are interested in buying the Betta fish with a beautiful tail and attractive color with a giant belly. Thus, the paper aims to build a Semantic Web with API of delivery services. We design a system to enable and increase the betta fish sales of the Yogyakarta Community, Indonesia. We construct an application with REST of a web semantics to retrieve various data, including places and shipping cost of items to enable buyers to estimate fish prices and shipping costs.